Linking information and people in a social system for academic conferences. Issue 2 (3rd April 2017) - Brusilovsky, Peter; Oh, Jung Sun; López, Claudia; Parra, Denis; Jeng, Wei
ABSTRACT: This paper investigates the feasibility of maintaining a social information system to support attendees at an academic conference. The main challenge of this work was to create an infrastructure where users' social activities, such as bookmarking, tagging, and social linking could be used to enhance user navigation and maximize the users' ability to locate two important types of information in conference settings: presentations to attend and attendees to meet. We developed Conference Navigator 3, a social conference support system that integrates a conference schedule planner with a social linking service. We examined its potential and functions in the context of a medium-scale academic conference. In this paper, we present the design of the system's socially enabled features and report the results of a conference-based study. Our study demonstrates the feasibility of social information systems for supporting academic conferences. Despite the low number of potential users and the short timeframe in which conferences took place, the usage of the system was high enough to provide sufficient data for social mechanisms. The study shows that most critical social features were highly appreciated and used, and provides direction for further research.